Disturbance ecology and biological diversity : scale, context, and nature - Beever, Erik A.; Prange, Suzanne; DellaSala, Dominick A. (Boca Raton : CRC Press, 2019)
'This book presents cascading effects of ecological disturbances on a multitude of ecosystem components. It includes agricultural development, large infrequent disturbances, forest harvesting, non-native grazing in deserts, ground transportation, powerline corridors, fires, urban ecology, disturbance in aquatic ecosystems, land-use dynamics on diversity, habitat fragmentation, sedimentation of wetlands, and contemporary climate change. The book facilitates users in understanding why disturbances are occurring while recommending mitigation and remediation strategies'--
Includes bibliographical references and index.
Keywords: Ecological disturbances; Biodiversity